2012
DOI: 10.1158/0008-5472.can-12-1166
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-Regulated Lentiviral TK/GCV Gene Therapy for Lung Cancer Treatment

Abstract: Nuclear factor erythroid-2 related factor 2 (Nrf2) is a transcription factor that regulates protection against a wide variety of toxic insults to cells, including cytotoxic cancer chemotherapeutic drugs. Many lung cancer cells harbor a mutation in either Nrf2 or its inhibitor Keap1 resulting in permanent activation of Nrf2 and chemoresistance. In this study, we sought to examine whether this attribute could be exploited in cancer suicide gene therapy by using a lentiviral (LV) vector expressing herpes simplex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Cancer cells with high ARE activity have been transferred with Nrf2-driven lentiviral vectors containing thymidine kinase (TK) and treated with a pro drug, ganciclovir (GCV). This enabled the killing of TK-containing tumour cells as well as neighbouring cells by the bystander effect (Leinonen et al 2012).…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…Cancer cells with high ARE activity have been transferred with Nrf2-driven lentiviral vectors containing thymidine kinase (TK) and treated with a pro drug, ganciclovir (GCV). This enabled the killing of TK-containing tumour cells as well as neighbouring cells by the bystander effect (Leinonen et al 2012).…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…Another alternative approach, known as cancer suicide gene therapy, has been applied to treat chemoresistant cancers with high NRF2 level (Leinonen et al, 2012). In vivo study has confirmed that the cancer suicide gene therapy can improve the DOX treatment.…”
Section: Novel Nrf2 Targeted Strategiesmentioning
confidence: 99%
“…Another strategy makes use of increased Nrf2 expression in cancer cells utilizing a lentiviral vector having several antioxidant response elements (ARE) derived from human glutamate-cysteine ligase modifier subunit (GCLM) gene controlling the expression of the transgene [27,49] . Nrf2 hyperactivity has been found to be extremely common in both lung adenocarcinoma as well as squamous cell carcinoma [50,51] …”
Section: Gene Therapy Applications Targeting Nrf2 In Cancermentioning
confidence: 99%